Compassion, collaboration and cultural-responsiveness: insights on promoting successful pathways through education for students who face school attendance barriers - O’Toole, Catriona; Ćirić, Tara (Frontiers in Education, 2024)
IntroductionWith concerns about school attendance problems (SAPs) increasing across the globe, this study sought to explore the varied experiences of young people, parents and practitioners, to uncover barriers to attendance and explore the responses and interventions that support successful pathways for students with school attendance challenges. The study, conducted in Limerick, Ireland, was concerned with participants’ lived experiences, including their experiences of themselves, of their interactions and relationships, and of the complex patterns that co-arise between themselves and the larger systemic context. It was informed by a trauma-informed conceptual framework, known as EMBRACE.MethodsFour cohorts of participants were purposively sampled: (1) educators (n = 15; school leaders, teachers, alternative education staff), (2) allied professionals (n = 12; psychologists, social workers, community workers etc.), (3) parents (n = 2, both mothers), and (4) young people (n = 11, aged 14–18 years). Online focus groups were conducted with the professional groups. In-person interviews were carried out with parents. The young people participated in either individual interviews or focus group interviews and arts-based methods (self-portraiture and body mapping) were used to facilitate thoughtful, embodied communication in a safe and supportive space. Data was analysed using reflective thematic analysis, with professionals’ data analysed separately to that of parents and young people.ResultsThe findings indicated that successful resolution of SAPs depends on the creation of an inclusive, responsive, and flexible mainstream education system, that can meet the needs of diverse learners within a fully resourced continuum of support model. In addition, alternative education pathways (including home tuition and online provision) were considered vital. This study reaffirms the importance of creating space for interagency collaboration and for forging strong relationships characterised by compassion, trust and mutuality, at all levels - between children and young people, parents/carers, colleagues, educators and professionals in other organisations. A special focus is required to help address inordinate structural barriers faced by disenfranchised groups (including the Traveller community in the Irish context).DiscussionBy ensuring that students are listened to, believed, and empowered to actively participate in shaping their educational experiences, it is possible to create successful educational pathways for all students, regardless of their background or circumstances.